2021
DOI: 10.1053/j.jvca.2020.11.024
|View full text |Cite
|
Sign up to set email alerts
|

PECS II Block Combined with Supraclavicular Brachial Plexus Block Allows Anesthesia for Transaxillary Thoracic Outlet Syndrome Decompression Surgery

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Also anatomical variations such as a postfixed brachial plexus (eg T1 and T2 are anastomosed to the brachial plexus) could interfere with the extent of the clinical effect of the interpectoral-pectoserratus plane block on postoperative pain in our patients [27]. This may also explain the results of da Costa et al, who combined an interpectoral-pectoserratus plane block with a supraclavicular plexus block, which does provide analgesia of the shoulder [28]. However, a major drawback of this approach is phrenic nerve paresis which occurs in up to 45% of cases after supraclavicular plexus block [29].…”
Section: Tablementioning
confidence: 86%
“…Also anatomical variations such as a postfixed brachial plexus (eg T1 and T2 are anastomosed to the brachial plexus) could interfere with the extent of the clinical effect of the interpectoral-pectoserratus plane block on postoperative pain in our patients [27]. This may also explain the results of da Costa et al, who combined an interpectoral-pectoserratus plane block with a supraclavicular plexus block, which does provide analgesia of the shoulder [28]. However, a major drawback of this approach is phrenic nerve paresis which occurs in up to 45% of cases after supraclavicular plexus block [29].…”
Section: Tablementioning
confidence: 86%
“…When the proper skills for ultrasound machine handling are achieved, the appropriate knowledge of the relevant anatomy allows the anesthesiologist to tailor the analgesia over the surgical requirements, accomplishing a complete analgesia field by adding pieces, one over another, like a jigsaw puzzle (2). As an example, adding an interpectoral block with a parasternal block and a pecto-serratus block, allows completion of the field of analgesia for modified radical mastectomies, as well as the combination of a pecto-serratus block with a supraclavicular block of the brachial plexus, allows to obtain surgical analgesia for a trans-axillary correction of the thoracic outlet syndrome (3).…”
Section: Editorial On the Research Topic Interfascial Plane Blocksmentioning
confidence: 99%
“…16 A limited number of case reports have shown that PECS blocks alone or in combination with other nerve blocks can provide intraoperative analgesia and anesthesia. [17][18][19][20][21] The aim of this study was to evaluate the feasibility of the PECS II block for CIED insertion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that PECS blocks can be used as part of multimodal analgesia not only after breast surgery but also after cardiac 12 and thoracic surgery, 13–15 and venous catheter port implantation 16 . A limited number of case reports have shown that PECS blocks alone or in combination with other nerve blocks can provide intraoperative analgesia and anesthesia 17–21 . The aim of this study was to evaluate the feasibility of the PECS II block for CIED insertion.…”
Section: Introductionmentioning
confidence: 99%